Understanding morphological degradation of Ag nanoparticle during electrochemical CO2 reduction reaction by identical location observation. (1st March 2021) - Yun, Hyewon; Kim, Jiwon; Choi, Woong; Han, Man Ho; Park, Jong Hyeok; Oh, Hyung-suk; Won, Da Hye; Kwak, Kyungwon; Hwang, Yun Jeong
Abstract: Electrocatalytic systems affording stable performance beyond the initial catalytic activity and selectivity have been actively discussed. Understanding the long-term stability of nanoparticle catalysts requires careful monitoring of the morphological changes. Herein, we demonstrate the relationship between the degradation of the catalytic activity and morphological changes in Ag nanoparticles during the electrochemical CO2 reduction reaction (CO2 RR) for CO production by identical location transmission electron microscopy (IL-TEM) measurements. The synthesized Ag/C catalyst with 95.1% CO Faradaic efficiency ( FECO ) at −0.82 V vs. RHE showed a gradual decrease in the CO production current density and FECO, whereas the H2 production increased during 12 h of CO2 RR. IL-TEM images showed that small Ag particles with dimensions of less than 5 nm were newly formed from the original particles within 1 h of reaction, accounting for 80% of the total number of particles, and slowly grew to around 10 nm with multiple domains when the CO2 RR was prolonged. These morphological changes were explained in connection with the CO current density gradient, where it was proposed that the formation of small particles causes a sharp decrease in the CO production during the first hour, and subsequent growth of the Ag nanoparticles did not restore the CO2 RR activity of the particles. It was confirmed that degradation of the nanoparticles was more severe at a higher cathodic potential, and occurred during the CO2 RR, but not in the hydrogen evolution reaction (HER) in N2 -purged KHCO3 electrolyte. In this study, we introduce analytical methods for observing morphological changes of nanoparticles in the identical location during CO2 RR electrolysis. Graphical abstract: Image, graphical abstract